RESULTS AND ANALYSIS OF EXPERIMENTAL WORKS DIRECTED TO DEVELOP CREATIVE THINKING OF FUTURE PRIMARY EDUCATION TEACHERS (International Congress on Economics, Management and Business Studies, 2026)
This article covers the issues of creative thinking competence formation, which plays an important role in the professional-pedagogical training of future primary school teachers. In the study, the concept of innovative technological assignments, the methodology of their implementation in the educational process, and the content of the three-stage (determining, forming and checking) organized pedagogical experiments were analyzed in detail.
Keywords: creative thinking, innovative technological assignment, pedagogical experiment, divergent thinking, didactic games, case study, integrated education.